Estimasi Emisi Gas Rumah Kaca yang Dihasilkan dari Pembakaran Sampah di Jawa Tengah - Setyo Prabowo; Pranoto Pranoto; Sri Budiastuti (Universitas Sebelas Maret, 2017)
Climate change is no longer an issue but has become evident in environmental issues. The concentration of CO2 from year to year rises proportional to the increase in the earth's temperature. One of the components causing climate change is open burning solid waste. Burnt solid waste will produce GHG emissions in addition to affecting human health. Currently, there is no one in 35 districts/municipalities to process waste thoroughly in accordance with the requirements. The pattern of behavior in managing solid waste is carried out by the highest society by burning waste openly that is 42.07%. In this study the calculation of emissions by projecting emissions without any action of GHG emission reduction, action and emission reduction targets in 2010-2020 resulting from burning solid waste. The calculation of GHG emission levels for the waste sector in 35 districts/cities is done by referring to the method developed by IPCC 2006. The emissions generated in 2010-2020 from waste burning activities amounted to 1357,53 Gg CO2e or 24,72 % of the total emissions of the solid waste sector. Based on the results of research, the ability of Local Government of Regency/City to take action and plan of GHG emission reduction mitigation until 2020 to burning solid waste activity equal to 305,36 Gg CO2e. These types of actions include solid waste bank, solid waste house, 3R unit and thermal unit. The low target of the decline is due to budget constraints from the government so that the self-supporting role of the community, is necessary. The number of solid waste banks, 3R units and and the solid waste house of 2010-2016 as mitigation action amounted to 1462 units, 135 units and 458 units respectively. Meanwhile, the mitigation action plan for 2017-2020 through solid waste bank activities, 3R units, thermal unit are 1129 units, 177 units and 3 units.